SPLITTING AUTOMORPHISMS OF FREE BURNSIDE GROUPS - Atabekyan, V.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
We have proved, that if n≥1003 is an arbitrary odd number and φ is a splitting automorphism of period n of group B(m,n) that has a prime order, then φ is inner automorphism.